Psychometric properties of the mock interview rating scale for autistic transition-age youth - Smith, Matthew J.; Sherwood, Kari L.; Genova, Helen M.; Ross, Brittany; DaWalt, Leann Smith; Bishop, Lauren; Telfer, David; Brown, Cheryl; Sanchez, Barbara; Kallen, Michael A. (Frontiers in Psychiatry, 2023)
Background Employment is a major contributor to quality of life. However, autistic people are often unemployed and underemployed. One potential barrier to employment is the job interview. However, the availability of psychometrically-evaluated assessments of job interviewing skills is limited for autism services providers and researchers. Objective We analyzed the psychometric properties of the Mock Interview Rating Scale that was adapted for research with autistic transition-age youth (A-MIRS; a comprehensive assessment of video-recorded job interview role-play scenarios using anchor-based ratings for 14 scripted job scenarios). Methods Eighty-five transition-age youth with autism completed one of two randomized controlled trials to test the effectiveness of two interventions focused on job interview skills. All participants completed a single job interview role-play at pre-test that was scored by raters using the A-MIRS. We analyzed the structure of the A-MIRS using classical test theory, which involved conducting both exploratory and confirmatory factor analyzes, Rasch model analysis and calibration techniques. We then assessed internal consistency, inter-rater reliability, and test–retest reliability. Pearson correlations were used to assess the A-MIRS’ construct, convergent, divergent, criterion, and predictive validities by comparing it to demographic, clinical, cognitive, work history measures, and employment outcomes. Results Results revealed an 11-item unidimensional construct with strong internal consistency, inter-rater reliability, and test–retest reliability. Construct [pragmatic social skills (r = 0.61, p < 0.001), self-reported interview skills (r = 0.34, p = 0.001)], divergent [e.g., age (r = −0.13, p = 0.26), race (r = 0.02, p = 0.87)], and predictive validities [competitive employment (r = 0.31, p = 0.03)] received initial support via study correlations, while convergent [e.g., intrinsic motivation (r = 0.32, p = 0.007), job interview anxiety (r = −0.19, p = 0.08)] and criterion [e.g., prior employment (r = 0.22, p = 0.046), current employment (r = 0.21, p = 0.054)] validities were limited. Conclusion The psychometric properties of the 11-item A-MIRS ranged from strong-to-acceptable, indicating it may have utility as a reliable and valid method for assessing the job interview skills of autistic transition-age youth.